Campaigning in Quebec Municipal Elections: When the Party Defines Door to Door Canvassing as “The Right Way” to Campaign - Mévellec, Anne (Frontiers in Political Science, 2021)
Electoral campaigns are one of the key moments in political life. Yet, there is little Canadian work on this subject when it comes to municipal elections. However, the international literature on campaigning provides an opportunity for useful questions on the transformations of this aspect of local political life by bringing together political sociology and electoral sociology. That being said in this context, we present the results of an exploratory case study of campaigning in a municipal political party in a Canadian city, more specifically situated in the Province of Quebec. Municipal political parties are usually considered as electoral machines. It is therefore important to study in detail the way these organizations conduct election campaigns. More specifically, we are looking to explore how municipal political parties influence the campaign by providing electoral techniques. To achieve this, we closely examine the door to door canvassing strategy, which hints at what the party considers a “good campaigning” standard and helps us observe the behaviours of candidates and the different ways they fulfill the party’s requirements. It is therefore not a question of measuring the effectiveness of partisan electoral devices but of understanding how the party produces campaigning norms and puts them to work. The results presented here offer an original insight into the internal workings of a municipal political party—something that has never before been documented in the Canadian context. First, they help to open the black box that is municipal political parties and to better understand their internal modus operandi. Second, the results illustrate that election campaigning is still fundamentally based on one-on-one encounters.